A composite titanium yellow pigment and preparation method thereof

A composite titanium yellow pigment is developed by doping nano titanium dioxide with Cr/Fe, coating with calcium phosphate, and adding silk fibroin and calcium carbonate to enhance heat resistance and color performance, addressing the limitations of traditional yellow pigments and avoiding toxic metals.

CN118852893BActive Publication Date: 2024-12-20HUNAN HUIBANG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411338745.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-20
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Traditional yellow pigments lack heat resistance, light resistance, weather resistance, acid and alkali resistance, solvent resistance, and non-toxicity, making them unsuitable for high-performance environmentally friendly coatings and plastics, and the use of toxic metals like cadmium and lead is restricted.

Method used

A composite titanium yellow pigment is prepared by doping nano titanium dioxide with Cr/Fe, coating it with calcium phosphate, modifying with tannic acid, and depositing a composite material of regenerated silk fibroin, polyacrylic acid, and calcium carbonate to enhance properties such as tinting power, dispersibility, and durability.

Benefits of technology

The composite pigment exhibits improved heat resistance, durability, and color performance with bright and pearlescent colors, while avoiding the use of toxic metals, offering broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention proposes a composite titanium yellow pigment and a preparation method thereof, and belongs to the technical field of pigments. Cr / Fe doped nano titanium dioxide powder is prepared by a reverse emulsion method, calcium phosphate is coated on the surface of the Cr / Fe doped nano titanium dioxide powder, and after being modified by tannic acid, a composite material of regenerated silk fibroin, polyacrylic acid and calcium carbonate is deposited on the surface of the modified calcium phosphate coated Cr / Fe doped nano titanium dioxide to prepare a composite titanium yellow pigment. The composite titanium yellow pigment prepared by the invention has a simple preparation method and mild preparation conditions. The prepared pigment has bright color, pearlescent color, high color brightness, good dispersibility, improved heat resistance and durability of the pigment, better tinting power and better color performance, and at the same time, avoids the use of toxic metals such as cadmium and lead, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pigments, and in particular to a composite titanium yellow pigment and a preparation method thereof. Background Art

[0002] Yellow pigments can generally be divided into two categories: organic pigments and inorganic pigments. Traditional yellow pigments, whether organic or inorganic, do not have the properties of heat resistance, light resistance, weather resistance, acid and alkali resistance, solvent resistance, and non-toxicity and harmlessness to the human body and the environment. They cannot meet the requirements of high-performance environmentally friendly coatings and plastics industries. Titanium-based yellow pigments such as titanium nickel yellow have more comprehensive and excellent application performance and have become a substitute for non-environmentally friendly yellow pigments.

[0003] Titanium yellow pigment is a rutile mixed-phase pigment with TiO2 as the main component. According to the different types of color-producing metals added, titanium yellow can be divided into titanium nickel yellow, titanium chrome yellow and titanium iron yellow. In the production of titanium nickel yellow and titanium chrome yellow, non-color-producing metal oxides (such as antimony and tungsten oxides, mainly antimony oxide) are also introduced as adjusters. Titanium yellow pigment was developed more than 50 years ago. Due to the limitations of preparation technology, the obtained titanium yellow pigment has a large particle size, low tinting power, light color, poor dispersibility, dark hue, and high cost of use. For a long time, it has not been used in more practical applications. In recent years, with the improvement of environmental awareness and attention to health issues, governments of various countries have begun to restrict or prohibit the use of pigments containing toxic elements such as lead and cadmium in coatings, plastics and other manufactured products. Titanium yellow pigment has become an ideal substitute for these toxic pigments due to its non-toxic and environmentally friendly characteristics. As the market's requirements for pigment performance continue to increase, how to further improve titanium yellow pigment's tinting power, weather resistance and other performance indicators while maintaining its environmental protection characteristics is also a problem that the industry urgently needs to solve. Summary of the invention

[0004] The purpose of the present invention is to provide a composite titanium yellow pigment and a preparation method thereof. The preparation method is simple and the preparation conditions are mild. The prepared pigment has bright color, pearlescent color, high color brightness, good dispersibility, improved heat resistance and durability of the pigment, better tinting power and better color performance. At the same time, the use of toxic metals such as cadmium and lead is avoided, and the pigment has broad application prospects.

[0005] The technical solution of the present invention is achieved in this way:

[0006] The invention provides a preparation method of a composite titanium yellow pigment. The invention comprises the following steps: preparing Cr / Fe doped nano titanium dioxide powder by an inverse emulsion method, coating the surface of the Cr / Fe doped nano titanium dioxide powder with calcium phosphate, modifying the surface of the Cr / Fe doped nano titanium dioxide powder with tannic acid, and then depositing a composite material of regenerated silk fibroin, polyacrylic acid and calcium carbonate on the surface of the modified calcium phosphate coated Cr / Fe doped nano titanium dioxide to prepare the composite titanium yellow pigment.

[0007] As a further improvement of the present invention, the following steps are included:

[0008] S1. Preparation of Cr / Fe doped nano-titanium dioxide: cyclohexane, surfactant system and water were mixed evenly, tetrabutyl titanate, chromium salt and iron salt were added, pH value was adjusted, reaction was stirred, centrifuged, washed, dried and calcined to obtain Cr / Fe doped nano-titanium dioxide powder;

[0009] S2. Calcium phosphate coating: Cr / Fe-doped nano-titanium dioxide powder was added to water, calcium salt, sodium phosphate and sodium hydroxide were added, the reaction was heated and stirred, centrifuged, washed and dried to obtain calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide;

[0010] S3. Modification: adding calcium phosphate coated Cr / Fe doped nano-titanium dioxide to a Tris-HCl solution, adding tannic acid, heating and stirring the reaction, centrifuging, washing, and drying to obtain modified calcium phosphate coated Cr / Fe doped nano-titanium dioxide;

[0011] S4. Preparation of regenerated silk fibroin solution: adding mulberry silk to a sodium carbonate solution, heating and boiling to degumming, filtering, dissolving in a lithium bromide solution, dialyzing, filtering, and obtaining a regenerated silk fibroin solution;

[0012] S5. Preparation of composite titanium yellow pigment: add calcium carbonate to water, introduce carbon dioxide, filter, continue to introduce carbon dioxide, dilute the solution to obtain a supersaturated calcium carbonate solution, add the regenerated silk fibroin solution, polyacrylic acid and magnesium salt prepared in step S4, add modified calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide, heat and stir to react, centrifuge, wash, and dry to obtain a composite titanium yellow pigment.

[0013] As a further improvement of the present invention, the mass ratio of cyclohexane, surfactant system, water, tetrabutyl titanate, chromium salt and iron salt in step S1 is (18-22): (3-5): (2-4): (2-3): (0.05-0.1): (0.03-0.05), the pH value is adjusted to 9.5-10.5, the stirring reaction time is 2-4 hours, the calcination temperature is 450-550°C, the time is 1-3 hours, the iron salt is selected from at least one of ferric chloride, ferric sulfate and ferric nitrate, the chromium salt is chromium nitrate, the surfactant system includes Tween and n-hexanol in a mass ratio of 5-7:2, and the Tween is selected from at least one of Tween-20, Tween-40, Tween-60 and Tween-80.

[0014] As a further improvement of the present invention, the mass ratio of the Cr / Fe-doped nano-titanium dioxide, calcium salt, sodium phosphate and sodium hydroxide in step S2 is 10: (1.2-1.3): (0.8-0.9): (0.3-0.4), the temperature of the heating and stirring reaction is 70-80°C, the time is 4-6h, and the calcium salt is selected from at least one of calcium chloride or calcium nitrate.

[0015] As a further improvement of the present invention, in step S3, the mass ratio of the calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide and tannic acid is 10:1-2, the pH value of the Tris-HCl solution is 8.5-9.5, the temperature of the heating and stirring reaction is 40-50°C, and the time is 1-2h.

[0016] As a further improvement of the present invention, the concentration of the sodium carbonate solution in step S4 is 0.3-0.7wt%, the heating and boiling degumming time is 30-50min, the concentration of the lithium bromide solution is 9-10mol / L, the dialysis bag pore size used in the dialysis is 12-14Kda, and the time is 2-4d.

[0017] As a further improvement of the present invention, the solution is diluted in step S5 until the calcium ion concentration in the solution is 7.5-8.5 mmol / L, the ventilation rate of the carbon dioxide is 10-20 mL / min, the temperature of the heating and stirring reaction is 30-35°C, the time is 24-36 hours, the mass ratio of the calcium carbonate, polyacrylic acid, magnesium salt and modified calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide is 0.3-0.5:1-2:0.5-1:10, and the magnesium salt is magnesium chloride or magnesium nitrate.

[0018] As a further improvement of the present invention, the present invention specifically comprises the following steps:

[0019] S1. Preparation of Cr / Fe doped nano titanium dioxide: 18-22 parts by weight of cyclohexane, 3-5 parts by weight of a surfactant system and 2-4 parts by weight of water are uniformly mixed, 2-3 parts by weight of tetrabutyl titanate, 0.05-0.1 parts by weight of a chromium salt, 0.03-0.05 parts by weight of an iron salt are added, the pH value is adjusted to 9.5-10.5, the reaction is stirred for 2-4 hours, centrifuged, washed, dried, and calcined at 450-550°C for 1-3 hours to obtain Cr / Fe doped nano titanium dioxide powder;

[0020] The surfactant system includes Tween and n-hexanol in a mass ratio of 5-7:2;

[0021] S2. Calcium phosphate coating: 10 parts by weight of Cr / Fe-doped nano-titanium dioxide powder was added to water, 1.2-1.3 parts by weight of calcium salt, 0.8-0.9 parts by weight of sodium phosphate and 0.3-0.4 parts by weight of sodium hydroxide were added, heated to 70-80°C, stirred for 4-6h, centrifuged, washed and dried to obtain calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide;

[0022] S3. Modification: 10 parts by weight of calcium phosphate coated Cr / Fe doped nano-titanium dioxide was added to a Tris-HCl solution having a pH value of 8.5-9.5, 1-2 parts by weight of tannic acid was added, heated to 40-50 ° C, stirred for 1-2 hours, centrifuged, washed, and dried to obtain a modified calcium phosphate coated Cr / Fe doped nano-titanium dioxide;

[0023] S4. Preparation of regenerated silk fibroin solution: Add mulberry silk to 0.3-0.7wt% sodium carbonate solution, heat and boil to degumming for 30-50min, filter, dissolve in 9-10mol / L lithium bromide solution, use a dialysis bag with a pore size of 12-14Kda for 2-4d, filter, and obtain a regenerated silk fibroin solution;

[0024] S5. Preparation of composite titanium yellow pigment: add 0.3-0.5 parts by weight of calcium carbonate to water, introduce carbon dioxide for 1-2 hours, filter, continue to introduce carbon dioxide for 1-2 hours, the ventilation rate of carbon dioxide is 10-20mL / min, dilute the solution until the calcium ion concentration in the solution is 7.5-8.5mmol / L, and prepare a supersaturated solution of calcium carbonate, add the regenerated silk protein solution prepared in step S4, 1-2 parts by weight of polyacrylic acid and 0.5-0.1 parts by weight of magnesium salt, add 10 parts by weight of modified calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide, heat to 30-35°C, stir the reaction for 24-36 hours, centrifuge, wash, and dry to prepare a composite titanium yellow pigment.

[0025] The present invention further protects a composite titanium yellow pigment prepared by the above preparation method.

[0026] The present invention has the following beneficial effects:

[0027] In the present invention, a surfactant system (Tween is a surfactant, n-hexanol is a co-surfactant), an organic solvent cyclohexane and water are mixed to form a reverse microemulsion, and reactants tetrabutyl titanate and ammonia water are added. The water core in the W / O microemulsion is surrounded by a monomolecular interface layer composed of a surfactant and a co-surfactant, and is dispersed in the oil phase cyclohexane. The size of the water core is about several to tens of nanometers. The water core can solubilize the reactant tetrabutyl titanate, and because it has a large interface area, the material exchange is carried out with a large flux, and it can be used as a microreactor for synthesizing nanoparticles, thereby preparing Cr / Fe doped nano titanium dioxide, Cr and Fe doping, Ti 4+ Low-priced Fe 3+ or Cr 3+ Replacement is used to maintain the electrical neutrality of the crystal and prevent electronic defects from causing changes in product color, which affects the electron transfer of the Ti-O bond and the crystal field energy of the TiO6 octahedron. It can well adjust the vividness and brightness of the pigment color, and has better color performance. At the same time, it also improves the heat resistance and durability of the pigment, and has better tinting power. At the same time, it avoids the use of toxic metals such as cadmium and lead.

[0028] The Cr / Fe doped nano titanium dioxide prepared by the present invention has many special properties compared with ordinary pigments due to the nano effect of its particles. It is a high-strength inorganic material. When distributed in an organic coating, it can toughen the particles, improve the friction and mechanical properties of the coating, and improve the wear resistance, hardness, failure strength and effective toughness of the coating.

[0029] The invention further improves the heat resistance and dispersibility of the iron oxide yellow pigment by coating the surface of the prepared Cr / Fe doped nano titanium dioxide with an inorganic substance calcium phosphate.

[0030] Subsequently, after modification with tannic acid, it is convenient for the loading and deposition of silk fibroin and nacreous calcium carbonate, so that the obtained pigment has a pearlescent color and good hue. Polyacrylic acid and magnesium ions are used to regulate the crystallization of calcium carbonate. The regenerated silk fibroin has good biocompatibility and adjustable biodegradability, and has excellent mechanical properties, thereby significantly improving the color brightness of the pigment and also improving the dispersibility.

[0031] The composite titanium yellow pigment prepared by the invention has a simple preparation method and mild preparation conditions; the prepared pigment has bright color, pearlescent color, high color brightness, good dispersibility, improved heat resistance and durability of the pigment, better tinting power and better color performance; meanwhile, the use of toxic metals such as cadmium and lead is avoided, and the pigment has broad application prospects. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] This embodiment provides a method for preparing a composite titanium yellow pigment, which specifically comprises the following steps:

[0035] S1. Preparation of Cr / Fe doped nano-titanium dioxide: 18 g cyclohexane, 3 g surfactant system and 2 g water were mixed evenly, 2 g tetrabutyl titanate, 0.05 g chromium nitrate and 0.03 g ferric nitrate were added, the pH value was adjusted to 9.5, the mixture was stirred for 2 h, centrifuged, washed, dried and calcined at 450 ° C for 1 h to obtain Cr / Fe doped nano-titanium dioxide;

[0036] The surfactant system includes Tween-20 and n-hexanol in a mass ratio of 5:2;

[0037] S2. Calcium phosphate coating: 10 g of Cr / Fe doped nano-titanium dioxide was added to 500 mL of water, 1.2 g of calcium chloride, 0.8 g of sodium phosphate and 0.3 g of NaOH were added, heated to 70 ° C, stirred for 4 h, centrifuged, washed and dried to obtain calcium phosphate coated Cr / Fe doped nano-titanium dioxide;

[0038] S3. Modification: 10 g of calcium phosphate coated Cr / Fe doped nano-titanium dioxide was added to a Tris-HCl solution with a pH value of 8.5, 1 g of tannic acid was added, the mixture was heated to 40°C, stirred for reaction for 1 h, centrifuged, washed, and dried to obtain modified calcium phosphate coated Cr / Fe doped nano-titanium dioxide;

[0039] S4. Preparation of regenerated silk fibroin solution: 10 g of mulberry silk was added to 500 mL of 0.3 wt% sodium carbonate solution, heated and boiled for degumming for 30 min, filtered, dissolved in 500 mL of 9 mol / L lithium bromide solution, dialyzed for 2 d using a dialysis bag with a pore size of 12 Kda, filtered, and a regenerated silk fibroin solution was obtained;

[0040] S5. Preparation of composite titanium yellow pigment: Add 0.3g calcium carbonate to 500mL water, introduce carbon dioxide for 1h, filter, continue to introduce carbon dioxide for 1h, the carbon dioxide ventilation rate is 10mL / min, dilute the solution until the calcium ion concentration in the solution is 7.5mmol / L, and prepare a supersaturated solution of calcium carbonate, add the regenerated silk protein solution prepared in step S4, 1g polyacrylic acid and 0.5g magnesium chloride, add 10g modified calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide, heat to 30°C, stir the reaction for 24h, centrifuge, wash, and dry to prepare a composite titanium yellow pigment.

[0041] Example 2

[0042] This embodiment provides a method for preparing a composite titanium yellow pigment, which specifically comprises the following steps:

[0043] S1. Preparation of Cr / Fe doped nano-titanium dioxide: 22 g cyclohexane, 5 g surfactant system and 4 g water were mixed evenly, 3 g tetrabutyl titanate, 0.1 g chromium nitrate and 0.05 g ferric nitrate were added, the pH value was adjusted to 10.5, the mixture was stirred for 4 h, centrifuged, washed, dried and calcined at 550 ° C for 3 h to obtain Cr / Fe doped nano-titanium dioxide;

[0044] The surfactant system includes Tween-60 and n-hexanol in a mass ratio of 7:2;

[0045] S2. Calcium phosphate coating: 10 g of Cr / Fe doped nano-titanium dioxide was added to 500 mL of water, 1.3 g of calcium chloride, 0.9 g of sodium phosphate and 0.4 g of NaOH were added, heated to 80 ° C, stirred for 6 h, centrifuged, washed and dried to obtain calcium phosphate coated Cr / Fe doped nano-titanium dioxide;

[0046] S3. Modification: 10 g of calcium phosphate coated Cr / Fe doped nano-titanium dioxide was added to a Tris-HCl solution with a pH value of 9.5, 2 g of tannic acid was added, the solution was heated to 50°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified calcium phosphate coated Cr / Fe doped nano-titanium dioxide;

[0047] S4. Preparation of regenerated silk fibroin solution: 10 g of mulberry silk was added to 500 mL of 0.7 wt% sodium carbonate solution, heated and boiled for degumming for 50 min, filtered, dissolved in 500 mL of 10 mol / L lithium bromide solution, dialyzed for 4 d using a dialysis bag with a pore size of 14 Kda, filtered, and a regenerated silk fibroin solution was obtained;

[0048] S5. Preparation of composite titanium yellow pigment: Add 0.5g calcium carbonate to 500mL water, introduce carbon dioxide for 2h, filter, continue to introduce carbon dioxide for 2h, the carbon dioxide ventilation rate is 20mL / min, dilute the solution until the calcium ion concentration in the solution is 8.5mmol / L, and prepare a supersaturated solution of calcium carbonate, add the regenerated silk protein solution prepared in step S4, 2g polyacrylic acid and 0.1g magnesium chloride, add 10g modified calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide, heat to 35°C, stir the reaction for 36h, centrifuge, wash, and dry to prepare a composite titanium yellow pigment.

[0049] Example 3

[0050] This embodiment provides a method for preparing a composite titanium yellow pigment, which specifically comprises the following steps:

[0051] S1. Preparation of Cr / Fe doped nano-titanium dioxide: 20 g cyclohexane, 4 g surfactant system and 3 g water were mixed evenly, 2.5 g tetrabutyl titanate, 0.07 g chromium nitrate and 0.04 g ferric nitrate were added, the pH value was adjusted to 10, stirred for 3 h, centrifuged, washed, dried and calcined at 500 ° C for 2 h to obtain Cr / Fe doped nano-titanium dioxide;

[0052] The surfactant system includes Tween-80 and n-hexanol in a mass ratio of 6:2;

[0053] S2. Calcium phosphate coating: 10 g of Cr / Fe doped nano-titanium dioxide was added to 500 mL of water, 1.24 g of calcium chloride, 0.85 g of sodium phosphate and 0.36 g of NaOH were added, heated to 75 ° C, stirred for 5 h, centrifuged, washed and dried to obtain calcium phosphate coated Cr / Fe doped nano-titanium dioxide;

[0054] S3. Modification: 10 g of calcium phosphate coated Cr / Fe doped nano-titanium dioxide was added to a Tris-HCl solution with a pH value of 9, 1.5 g of tannic acid was added, the mixture was heated to 45°C, stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain modified calcium phosphate coated Cr / Fe doped nano-titanium dioxide;

[0055] S4. Preparation of regenerated silk fibroin solution: 10 g of mulberry silk was added to 500 mL of 0.5 wt% sodium carbonate solution, heated and boiled for 40 min, filtered, dissolved in 500 mL of 9.5 mol / L lithium bromide solution, dialyzed for 3 d using a dialysis bag with a pore size of 13 Kda, filtered, and a regenerated silk fibroin solution was obtained;

[0056] S5. Preparation of composite titanium yellow pigment: Add 0.4g calcium carbonate to 500mL water, introduce carbon dioxide for 1.5h, filter, continue to introduce carbon dioxide for 1.5h, the carbon dioxide ventilation rate is 15mL / min, dilute the solution until the calcium ion concentration in the solution is 8mmol / L, and prepare a supersaturated solution of calcium carbonate, add the regenerated silk protein solution prepared in step S4, 1.2g polyacrylic acid and 0.7g magnesium chloride, add 10g modified calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide, heat to 32°C, stir the reaction for 30h, centrifuge, wash, and dry to prepare a composite titanium yellow pigment.

[0057] Comparative Example 1

[0058] Compared with Example 3, the difference is that chromium nitrate is not added in step S1.

[0059] The details are as follows:

[0060] S1. Preparation of Fe-doped nano-titanium dioxide: 20 g of cyclohexane, 4 g of surfactant system and 3 g of water were mixed evenly, 2.5 g of tetrabutyl titanate and 0.11 g of ferric nitrate were added, the pH value was adjusted to 10, the reaction was stirred for 3 h, centrifuged, washed, dried, and calcined at 500 ° C for 2 h to obtain Fe-doped nano-titanium dioxide;

[0061] The surfactant system includes Tween-80 and n-hexanol in a mass ratio of 6:2.

[0062] Comparative Example 2

[0063] Compared with Example 3, the difference is that no ferric nitrate is added in step S1.

[0064] The details are as follows:

[0065] S1. Preparation of Cr-doped nano-titanium dioxide: 20 g of cyclohexane, 4 g of surfactant system and 3 g of water were mixed evenly, 2.5 g of tetrabutyl titanate and 0.11 g of chromium nitrate were added, the pH value was adjusted to 10, the reaction was stirred for 3 h, centrifuged, washed, dried, and calcined at 500 ° C for 2 h to obtain Cr-doped nano-titanium dioxide;

[0066] The surfactant system includes Tween-80 and n-hexanol in a mass ratio of 6:2.

[0067] Comparative Example 3

[0068] Compared with Example 3, the difference is that step S2 is not performed.

[0069] The details are as follows:

[0070] S1. Preparation of Cr / Fe doped nano-titanium dioxide: 20 g cyclohexane, 4 g surfactant system and 3 g water were mixed evenly, 2.5 g tetrabutyl titanate, 0.07 g chromium nitrate and 0.04 g ferric nitrate were added, the pH value was adjusted to 10, stirred for 3 h, centrifuged, washed, dried and calcined at 500 ° C for 2 h to obtain Cr / Fe doped nano-titanium dioxide;

[0071] The surfactant system includes Tween-80 and n-hexanol in a mass ratio of 6:2;

[0072] S2. Modification: 10 g of Cr / Fe-doped nano-titanium dioxide was added to a Tris-HCl solution with a pH value of 9, 1.5 g of tannic acid was added, the mixture was heated to 45°C, stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain modified Cr / Fe-doped nano-titanium dioxide;

[0073] S3. Preparation of regenerated silk fibroin solution: 10 g of mulberry silk was added to 500 mL of 0.5 wt% sodium carbonate solution, heated and boiled for 40 min, filtered, dissolved in 500 mL of 9.5 mol / L lithium bromide solution, dialyzed for 3 d using a dialysis bag with a pore size of 13 Kda, filtered, and a regenerated silk fibroin solution was obtained;

[0074] S4. Preparation of composite titanium yellow pigment: Add 0.4g calcium carbonate to 500mL water, introduce carbon dioxide for 1.5h, filter, continue to introduce carbon dioxide for 1.5h, the carbon dioxide ventilation rate is 15mL / min, dilute the solution until the calcium ion concentration in the solution is 8mmol / L, and prepare a supersaturated solution of calcium carbonate, add the regenerated silk protein solution prepared in step S3, 1.2g polyacrylic acid and 0.7g magnesium chloride, add 10g modified Cr / Fe doped nano titanium dioxide, heat to 32°C, stir the reaction for 30h, centrifuge, wash, and dry to prepare a composite titanium yellow pigment.

[0075] Comparative Example 4

[0076] Compared with Example 3, the difference is that step S3 is not performed.

[0077] The details are as follows:

[0078] S1. Preparation of Cr / Fe doped nano-titanium dioxide: 20 g cyclohexane, 4 g surfactant system and 3 g water were mixed evenly, 2.5 g tetrabutyl titanate, 0.07 g chromium nitrate and 0.04 g ferric nitrate were added, the pH value was adjusted to 10, stirred for 3 h, centrifuged, washed, dried and calcined at 500 ° C for 2 h to obtain Cr / Fe doped nano-titanium dioxide;

[0079] The surfactant system includes Tween-80 and n-hexanol in a mass ratio of 6:2;

[0080] S2. Calcium phosphate coating: 10 g of Cr / Fe doped nano-titanium dioxide was added to 500 mL of water, 1.24 g of calcium chloride, 0.85 g of sodium phosphate and 0.36 g of NaOH were added, heated to 75 ° C, stirred for 5 h, centrifuged, washed and dried to obtain calcium phosphate coated Cr / Fe doped nano-titanium dioxide;

[0081] S3. Preparation of regenerated silk fibroin solution: 10 g of mulberry silk was added to 500 mL of 0.5 wt% sodium carbonate solution, heated and boiled for 40 min, filtered, dissolved in 500 mL of 9.5 mol / L lithium bromide solution, dialyzed for 3 d using a dialysis bag with a pore size of 13 Kda, filtered, and a regenerated silk fibroin solution was obtained;

[0082] S4. Preparation of composite titanium yellow pigment: Add 0.4g calcium carbonate to 500mL water, introduce carbon dioxide for 1.5h, filter, continue to introduce carbon dioxide for 1.5h, the carbon dioxide ventilation rate is 15mL / min, dilute the solution until the calcium ion concentration in the solution is 8mmol / L, and prepare a supersaturated solution of calcium carbonate, add the regenerated silk protein solution prepared in step S3, 1.2g polyacrylic acid and 0.7g magnesium chloride, add 10g calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide, heat to 32°C, stir the reaction for 30h, centrifuge, wash, and dry to prepare a composite titanium yellow pigment.

[0083] Comparative Example 5

[0084] Compared with Example 3, the difference is that steps S3 to S5 are not performed.

[0085] The details are as follows:

[0086] S1. Preparation of Cr / Fe doped nano-titanium dioxide: 20 g cyclohexane, 4 g surfactant system and 3 g water were mixed evenly, 2.5 g tetrabutyl titanate, 0.07 g chromium nitrate and 0.04 g ferric nitrate were added, the pH value was adjusted to 10, stirred for 3 h, centrifuged, washed, dried and calcined at 500 ° C for 2 h to obtain Cr / Fe doped nano-titanium dioxide;

[0087] The surfactant system includes Tween-80 and n-hexanol in a mass ratio of 6:2;

[0088] S2. Calcium phosphate coating: Add 10g Cr / Fe doped nano titanium dioxide into 500mL water, add 1.24g calcium chloride, 0.85g sodium phosphate and 0.36g NaOH, heat to 75°C, stir and react for 5h, centrifuge, wash and dry to obtain calcium phosphate coated Cr / Fe doped nano titanium dioxide, which is a composite titanium yellow pigment.

[0089] Test Example 1 Heat Resistance Analysis

[0090] The heat resistance of Examples 1-3 of the present invention, Comparative Examples 1-5 and commercially available titanium yellow pigment was tested.

[0091] The heat resistance of the pigment was tested according to the standard HG / T3853-2006 pigment dry powder heat resistance determination method. A crucible containing 2.0g of the sample to be tested was placed in a 250℃ oven, taken out after 30 minutes, and cooled. A CM-5 colorimeter was used to measure the color change of the sample before and after baking. Calculated according to the Hunter color difference formula:

[0092] ΔE=[ΔL 2 +Δa 2 +Δb 2 ] 1 / 2

[0093] Among them: ΔL=L'-L, + means white, - means dark; Δa=a'-a, + means red, - means green; Δb=b'-b, + means yellow, - means bluish. L and L' respectively represent the brightness value of the pigment before and after baking; a and a' respectively represent the red / green value of the pigment before and after baking; b and b' respectively represent the yellow / blue value of the pigment before and after baking.

[0094] The results are shown in Table 1.

[0095] Table 1

[0096]

[0097] It can be seen from the above table that the composite titanium yellow pigments prepared in Examples 1-3 of the present invention have better heat resistance.

[0098] Test Example 2 Analysis of Color Properties of Pigments

[0099] The performance tests were performed on Examples 1-3 of the present invention and Comparative Examples 1-5.

[0100] The CIEL of the obtained samples was measured using the ADCI-60-C fully automatic colorimeter produced by Beijing Chentai Instrument Technology Co., Ltd. * a * b * Value, where L * is the brightness measurement value, a * is the red-green value, b *is the yellow-blue measurement value. Experimental parameters: lighting condition 0 / d, test method is reflection, standard illuminant is D65, standard observer 10° field of view, test aperture φ12 / 22mm, results are shown in Table 2. The CIEL*a*b* system is based on the CIELab system, supplemented by the statistical correction of human eye's color perception, thus forming a real color standard system. Among them, L* represents brightness, and its value ranges from 0-100, indicating the grayscale change from black to white; according to the nature that red and green and yellow and blue cannot coexist with each other, the colors are divided into the red-green a* axis and the yellow-blue b* axis, among which +a* is the red phase, -a* is the green phase, +b* is the yellow phase, and -b* is the blue phase. The larger the absolute value of each value, the darker the corresponding hue.

[0101] Table 2

[0102]

[0103] It can be seen from the above table that the composite titanium yellow pigment prepared in Examples 1-3 of the present invention has better color performance.

[0104] Test Example 3 Dispersion Test

[0105] The performance of Examples 1-3 of the present invention, Comparative Examples 1-5 and commercially available titanium yellow pigment were tested.

[0106] Weigh 0.01g of powder and place it in 10mL of anhydrous ethanol solvent. After ultrasonication for 5 minutes, use a pipette to transfer 1mL of the above suspension to a 25mL volumetric flask, dilute with anhydrous ethanol, and ultrasonicate for 5 minutes. Finally, test the absorbance value at 450nm. Repeat the measurement three times for each sample and take the average value. The higher the absorbance value, the better the dispersibility of the sample and the better the modification effect.

[0107] The results are shown in Table 3.

[0108] Table 3

[0109]

[0110] It can be seen from the above table that the composite titanium yellow pigment prepared in Examples 1-3 of the present invention has better dispersibility.

[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite titanium yellow pigment, characterized in that: The Cr / Fe doped nano titanium dioxide powder is prepared by an inverse emulsion method, calcium phosphate is coated on the surface of the Cr / Fe doped nano titanium dioxide powder, and after being modified by tannic acid, a composite material of regenerated silk fibroin, polyacrylic acid and calcium carbonate is deposited on the surface of the modified calcium phosphate coated Cr / Fe doped nano titanium dioxide to prepare a composite titanium yellow pigment, which specifically comprises the following steps: S1. Preparation of Cr / Fe doped nano titanium dioxide: cyclohexane, surfactant system and water are mixed evenly, tetrabutyl titanate, chromium salt and iron salt are added, pH value is adjusted, stirring reaction is performed, centrifugation is performed, washing, drying and calcination are performed to obtain Cr / Fe doped nano titanium dioxide powder, wherein the mass ratio of cyclohexane, surfactant system, water, tetrabutyl titanate, chromium salt and iron salt is (18-22): (3-5): (2-4): (2-3): (0.05-0.1): (0.03-0.05); S2. Calcium phosphate coating: adding Cr / Fe doped nano titanium dioxide powder to water, adding calcium salt, sodium phosphate and sodium hydroxide, heating and stirring to react, centrifuging, washing and drying to obtain calcium phosphate coated Cr / Fe doped nano titanium dioxide, wherein the mass ratio of the Cr / Fe doped nano titanium dioxide, calcium salt, sodium phosphate and sodium hydroxide is 10: (1.2-1.3): (0.8-0.9): (0.3-0.4); S3 modification: adding calcium phosphate coated Cr / Fe doped nano-titanium dioxide to a Tris-HCl solution, adding tannic acid, heating and stirring the reaction, centrifuging, washing, and drying to obtain a modified calcium phosphate coated Cr / Fe doped nano-titanium dioxide, wherein the mass ratio of the calcium phosphate coated Cr / Fe doped nano-titanium dioxide to tannic acid is 10: 1-2; S4. Preparation of regenerated silk fibroin solution: adding mulberry silk to a sodium carbonate solution, heating and boiling to degumming, filtering, dissolving in a lithium bromide solution, dialyzing, filtering, and obtaining a regenerated silk fibroin solution; S5. Preparation of composite titanium yellow pigment: add calcium carbonate to water, introduce carbon dioxide, filter, continue to introduce carbon dioxide, dilute the solution to obtain a supersaturated calcium carbonate solution, add the regenerated silk fibroin solution, polyacrylic acid and magnesium salt obtained in step S4, add modified calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide, heat and stir to react, centrifuge, wash, and dry to obtain a composite titanium yellow pigment, wherein the mass ratio of the calcium carbonate, polyacrylic acid, magnesium salt and modified calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide is 0.3-0.5:1-2:0.5-1:

10.

2. The preparation method according to claim 1, characterized in that: The pH value in step S1 is adjusted to 9.5-10.5, the stirring reaction time is 2-4 hours, the calcination temperature is 450-550°C, the time is 1-3 hours, the iron salt is selected from at least one of ferric chloride, ferric sulfate, and ferric nitrate, the chromium salt is chromium nitrate, the surfactant system includes Tween and n-hexanol in a mass ratio of 5-7:2, and the Tween is selected from at least one of Tween-20, Tween-40, Tween-60, and Tween-80.

3. The preparation method according to claim 1, characterized in that: The temperature of the heating and stirring reaction in step S2 is 70-80° C., the time is 4-6 hours, and the calcium salt is selected from at least one of calcium chloride or calcium nitrate.

4. The preparation method according to claim 1, characterized in that: The pH value of the Tris-HCl solution in step S3 is 8.5-9.5, the temperature of the heating and stirring reaction is 40-50° C., and the time is 1-2 h.

5. The preparation method according to claim 1, characterized in that: The concentration of the sodium carbonate solution in step S4 is 0.3-0.7wt%, the heating and boiling degumming time is 30-50min, the concentration of the lithium bromide solution is 9-10mol / L, the dialysis bag pore size used in the dialysis is 12-14Kda, and the time is 2-4d.

6. The preparation method according to claim 1, characterized in that: In step S5, the solution is diluted to a calcium ion concentration of 7.5-8.5 mmol / L, the carbon dioxide ventilation rate is 10-20 mL / min, the temperature of the heating and stirring reaction is 30-35° C., the time is 24-36 h, and the magnesium salt is magnesium chloride or magnesium nitrate.

7. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Preparation of Cr / Fe doped nano titanium dioxide: 18-22 parts by weight of cyclohexane, 3-5 parts by weight of surfactant system and 2-4 parts by weight of water are mixed evenly, 2-3 parts by weight of tetrabutyl titanate, 0.05-0.1 parts by weight of chromium salt and 0.03-0.05 parts by weight of iron salt are added, pH value is adjusted to 9.5-10.5, stirring reaction is carried out for 2-4 hours, centrifugation, washing, drying, calcining at 450-550°C for 1-3 hours to obtain Cr / Fe doped nano titanium dioxide powder; The surfactant system includes Tween and n-hexanol in a mass ratio of 5-7:2; S2. Calcium phosphate coating: 10 parts by weight of Cr / Fe-doped nano-titanium dioxide powder was added to water, 1.2-1.3 parts by weight of calcium salt, 0.8-0.9 parts by weight of sodium phosphate and 0.3-0.4 parts by weight of sodium hydroxide were added, heated to 70-80°C, stirred for 4-6h, centrifuged, washed and dried to obtain calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide; S3. Modification: 10 parts by weight of calcium phosphate coated Cr / Fe doped nano-titanium dioxide was added to a Tris-HCl solution having a pH value of 8.5-9.5, 1-2 parts by weight of tannic acid was added, heated to 40-50 ° C, stirred for 1-2 hours, centrifuged, washed, and dried to obtain a modified calcium phosphate coated Cr / Fe doped nano-titanium dioxide; S4. Preparation of regenerated silk fibroin solution: Add mulberry silk to 0.3-0.7wt% sodium carbonate solution, heat and boil to degumming for 30-50min, filter, dissolve in 9-10mol / L lithium bromide solution, use a dialysis bag with a pore size of 12-14Kda for 2-4d, filter, and obtain a regenerated silk fibroin solution; S5. Preparation of composite titanium yellow pigment: add 0.3-0.5 parts by weight of calcium carbonate to water, introduce carbon dioxide for 1-2 hours, filter, continue to introduce carbon dioxide for 1-2 hours, the ventilation rate of carbon dioxide is 10-20mL / min, dilute the solution until the calcium ion concentration in the solution is 7.5-8.5mmol / L, and prepare a supersaturated solution of calcium carbonate, add the regenerated silk fibroin solution prepared in step S4, 1-2 parts by weight of polyacrylic acid and 0.5-0.1 parts by weight of magnesium salt, add 10 parts by weight of modified calcium phosphate-coated Cr / Fe-doped nano-titanium dioxide, heat to 30-35°C, stir the reaction for 24-36 hours, centrifuge, wash, and dry to prepare a composite titanium yellow pigment.

8. A composite titanium yellow pigment obtained by the preparation method according to any one of claims 1 to 7.